Bimelic Hirayama Disease: Clinical Dilemma Solved by Imaging - Shalabh Jain; Siddharth Yadav; Swarna Gupta; Ritu Gupta (Case Reports in Medicine)
Hirayama disease (juvenile muscular atrophy of distal upper extremity) is a cervical myelopathy predominantly affecting adolescent males. It is characterized by progressive muscular weakness and atrophy of unilateral or asymmetrically bilateral distal upper limbs. We report a case of an 18-year-male painter, who presented with gradually progressive, symmetrical bilateral weakness of hands and forearm for the last two years. On the basis of clinical examination, a provisional diagnosis of lower motor neuron type of symmetrical distal weakness due to heavy metal intoxication was kept. However, imaging studies helped in making a definitive diagnosis of Hirayama disease. The patient was advised cervical collar, and there was no progression in symptoms after six months of followup. Due to the rarity of bilateral symmetrical involvement in Hirayama disease, it remains obscured or unsuspected clinically, and MRI plays a pivotal role in diagnosis.